Diet Modulates Adipose Tissue Oxidative Stress in a Murine Acute Chagas Model - Ayyappan, Janeesh Plakkal (JSM Atheroscler, 2017)
Chagas disease, also known as American trypanosomiasis, is a tropical parasitic disease caused by the protozoan Trypanosoma cruzi. T. cruzi targets adipose tissue, which serves as a reservoir of this parasite. T. cruzi infection of adipose tissue is characterized by increased lipolysis, oxidative stress, and parasitemia. High fat diet (HFD) decreases lipolysis and increases the survival rate in the mice infected with T. cruzi during acute infection. However, the effect of HFD on oxidative stress in adipose tissue has not been examined in detail. In the present study we evaluated the effect of HFD on oxidative stress markers in both white and brown adipose tissues (WAT and BAT) during acute infection. We used qPCR to examine the mRNA expression levels of genes involved in several antioxidant defence systems, such as those acting in ROS metabolism, peroxidases, and relevant oxygen transporter genes. The result of our study showed that HFD regulates the expression levels of oxidative stress genes in adipose tissues and that these effects are often different in WAT and BAT. For instance, while HFD down-regulated the levels of most antioxidant genes in both WAT and BAT, it differentially affected the expression pattern of genes involved in ROS metabolism (e.g. peroxidases) in WAT and BAT tissues of infected mice. Together with our previous studies, these findings show that infection and diet both regulate antioxidant enzymes and other oxidative stress defenses in mouse adipose tissues during acute T. cruzi infection.